S1_6_SpaceElevators - Walji, Sherali; Feetham, Luke; Holden, Josef; Gray, David (Physics Special Topics, 2009)
This paper examines the feasibility of a space elevator based on an examination of the tensile stress induced in a cable, constructed of carbon nanotubes, that extends from the surface of the earth at the equator, up to the point of geostationary orbit and above. The maximum stress induced in such a cable is calculated to be 67GPa, which is significantly less than the theoretical maximum strength of a carbon nanotube.